Recent Evolution of Logistic Spatial Patterns in Metropolitan Contexts: The Case of Madrilenian Urban Region - Solís-Trapero, Eloy; Plaza-Tabasco, Julio; Martínez Sánchez-Mateo, Héctor Samuel (Revista de Estudios Andaluces, 2019)
The logistic activity has been analysed by different approaches, but with a lack of attention to its impacts in the urban and spatial configuration. This work studies the logistic expansion in the Urban Region of Madrid, considering the geographical polarization and its preferential location in suburban and rural zones in the metropolitan area. The methodology considers three variables enlightening the spatial and temporal diffusion: workers and companies by municipality, logistic land use by province and different types of logistic land use. The results confirm the dissemination of logistics in metropolitan areas according to suburbanization and spread processes, at the same time appears new urban centralities as a consequence of the capitalist integration of the economy at different scales.